2014
DOI: 10.1063/1.4890622
|View full text |Cite
|
Sign up to set email alerts
|

Specific heat of twisted bilayer graphene: Engineering phonons by atomic plane rotations

Abstract: We have studied the phonon specific heat in single-layer, bilayer and twisted bilayer graphene. The calculations were performed using the Born-von Karman model of lattice dynamics for intralayer atomic interactions and spherically symmetric interatomic potential for interlayer interactions. We found that at temperature T<15 K, specific heat varies with temperature as T n , where n = 1 for graphene, n = 1.6 for bilayer graphene and n = 1.3 for the twisted bilayer graphene. The phonon specific heat reveals an in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 53 publications
(80 reference statements)
2
85
0
Order By: Relevance
“…In addition to a numerical solution we also provide a simple analytical formula for calculating c v (T) for graphene, BLG and T-BLG with parameters extracted from the Born-von Karman model of the lattice vibrations. We have earlier proposed a possibility of engineering phonon dispersion and materials properties by twisting of the atomic planes in T-BLG [23][24]. The first experimental studies of heat conduction in suspended T-BLG confirmed that twisting substantially reduces K owing to the increased scattering phase space available for phonons in T-BLG as compared to the Bernal-stacked BLG [25].…”
Section: Introductionmentioning
confidence: 87%
“…In addition to a numerical solution we also provide a simple analytical formula for calculating c v (T) for graphene, BLG and T-BLG with parameters extracted from the Born-von Karman model of the lattice vibrations. We have earlier proposed a possibility of engineering phonon dispersion and materials properties by twisting of the atomic planes in T-BLG [23][24]. The first experimental studies of heat conduction in suspended T-BLG confirmed that twisting substantially reduces K owing to the increased scattering phase space available for phonons in T-BLG as compared to the Bernal-stacked BLG [25].…”
Section: Introductionmentioning
confidence: 87%
“…It has been shown that phonon energies strongly depend on the interatomic force constants (IFCs)-fitting parameters of interatomic interactions, used in the majority of the models. Therefore a proper choice of interatomic force constants is crucial for the accurate description of phonon energy spectra and thermal conductivity in graphene, twisted graphene and graphene nanoribbons [1][2][3]44,86].…”
Section: Theory Of the Thermal Conductivity Of Graphene And Gnrmentioning
confidence: 99%
“…We employ the density functional tight-binding (DFTB) method 15 to describe graphene while the van der Waals (vdW) interaction between the sheet and the substrate is modelled with the 6-12 Lennard-Jones (LJ) potential V LJ ðrÞ ¼ 4 LJ ððr=rÞ 12 À ðr=rÞ 6 Þ. 16,29 The direction transverse to the step (y) is described by periodic boundary conditions using 8 k y -points in the DFTB force-constant calculations. The ends of the sheet are first left free to float at a fixed distance over the substrate, in order to find the correct bending geometry.…”
Section: 14mentioning
confidence: 99%